Designing Travel Pattern of Cultural Journey To Broaden Tourist Dispersion throughout Flores Island - Ismayanti Istanto; Ina Djamhur (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2021)
A travel pattern that can be suitable with the shift of travel behavior is a must, so as, the purpose of the study is: (1) to do curation cultural-based attraction overland Flores and (2) cluster them into a thematic travel pattern that suit the travel time, travel distance and tourist dispersion. Multi-destination model is used in designing the pattern based on data collected through survey, interview and FGD with stakeholders from eight region of Flores and analyzed through exploratory sequence method. The finding shows from initial 196 cultural based attration, only 35 points of interest matched and are ready to be visited as in favored by stakeholders. As multi-destination, travel pattern are constructed on en-route and base-camp pattern. Three theme, then, came as cluster of (1) weaving; (2) traditional village; and (3) gastronomic. Weaving tour routes is consisted of 10 attractions, traditional village is comprised of 12 attractions and gastronomic route is contained of 13 attractions. Implication of study are as for travel industry, many creation of tour ativities and packages can be made, and as for tourist, it is a guide to explore the overland of Flores with cultural thematic.